2018
DOI: 10.21276/apalm.1630
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biofilm formation by three different methods and its antibiogram with special reference to indwelling medical devices from a tertiary care hospital

Abstract: Biofilms are produced by both Gram-positive and Gramnegative bacteria. Enterococcus faecalis, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus viridans, Escherichia coli, Klebsiella pneumoniae, Proteus mirabilis and Pseudomonas aeruginosa are commonly associated with the production of biofilms. [4] The expression of biofilms in these bacteria is mainly determined by operons. Operons are the clusters of coregulated genes with related functions. The series of genes in an operon are transcribed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Siddhiqui et al reported that the CRA method is not appropriate for biofilm detection. Out of 112 clinical isolates, CRA detected only 14.25% as biofilm producers as compared to TM which detected 29.46% as biofilmforming bacteria [1]. The tube method also detected 38% isolates as biofilm producers.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Siddhiqui et al reported that the CRA method is not appropriate for biofilm detection. Out of 112 clinical isolates, CRA detected only 14.25% as biofilm producers as compared to TM which detected 29.46% as biofilmforming bacteria [1]. The tube method also detected 38% isolates as biofilm producers.…”
Section: Discussionmentioning
confidence: 87%
“…Test organisms were cultured on the CRA medium and incubated aerobically for 24 -48 h at 37 °C. Black colonies with a dry crystalline consistency indicated biofilm production [1].…”
Section: Congo Red Agar (Cra)mentioning
confidence: 99%